Alveolar Wound Healing and Ridge Remodeling After Tooth Extraction in the Rat: A Histologic, Radiographic, and Histometric Study - Guglielmotti, M. B.; Cabrini, Rómulo Luis (Elsevier, 1985)
Fil: Guglielmotti, M. B. Comisión Nacional de Energía Atómica; Argentina